2022
DOI: 10.1002/aur.2733
|View full text |Cite
|
Sign up to set email alerts
|

Combining voice and language features improves automated autism detection

Abstract: Variability in expressive and receptive language, difficulty with pragmatic language, and prosodic difficulties are all features of autism spectrum disorder (ASD). Quantifying language and voice characteristics is an important step for measuring outcomes for autistic people, yet clinical measurement is cumbersome and costly. Using natural language processing (NLP) methods and a harmonic model of speech, we analyzed language transcripts and audio recordings to automatically classify individuals as ASD or non‐AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 51 publications
1
25
1
Order By: Relevance
“…In previous work repetition proportion has consistently underperformed compared to other ALMs (MacFarlane et al, 2022;Salem et al, 2021); here this measure continues to be less consistent and reliable than any other. Our finding that unintelligible proportion is robust to the effect of sampling context could mean that it is an independent measure-a feature not altered by the individual in response to different language activities.…”
Section: Potential Advantages Of Almscontrasting
confidence: 57%
See 2 more Smart Citations
“…In previous work repetition proportion has consistently underperformed compared to other ALMs (MacFarlane et al, 2022;Salem et al, 2021); here this measure continues to be less consistent and reliable than any other. Our finding that unintelligible proportion is robust to the effect of sampling context could mean that it is an independent measure-a feature not altered by the individual in response to different language activities.…”
Section: Potential Advantages Of Almscontrasting
confidence: 57%
“…Interestingly, the ALMs which were more able to discriminate between ASD and non-ASD in previous work-um ratio (a slightly different but comparable measure of disfluency, as discussed in Methods), unintelligible proportion, and CPM, (MacFarlane et al, 2022;Salem et al, 2021)-are also the most consistent across sampling contexts. This result should be further explored by introducing a non-ASD comparison group to future context analysis studies.…”
Section: Potential Advantages Of Almsmentioning
confidence: 68%
See 1 more Smart Citation
“…Classifiers relying on these humandefined features have often reported promising performance in discriminating diagnosed individuals (e.g., with schizophrenia) from controls without any neuropsychiatric condition, with accuracies between 60% and 90% (see Parola, Simonsen, Bliksted, and Fusaroli [3], Koops, Brederoo, Boer, Nadema, Voppel, and Sommer [5], Fusaroli, Lambrechts, Bang, Bowler, and Gaigg [6], and Rybner, Jessen, Mortensen, et al [11] for an overview of existing studies). Furthermore, several studies have sought to combine the two modalities (speech, text) and found them to contain complementary information for the classification of neuropsychiatric conditions [1,21]. This complementarity may be due to the ability of text models to capture variations in word usage that are not captured by acoustic models, and the ability of acoustic models to identify variations in prosody (e.g.…”
Section: Previous Work On Vocal and Linguistic Markers Of Neuropsychi...mentioning
confidence: 99%
“…Machine learning is increasingly used to identify voice and text-based markers that complement current methods for screening and monitoring neuropsychiatric conditions [1,2]. However, while clinical assessment often requires the identification of one diagnosis amongst many with partially overlapping clinical features, virtually all machine learning studies of voice and text-based markers focus on simpler binary outcomes, i.e., patients with one specific diagnosis versus controls without any neuropsychiatric conditions [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%